SLR: Discovering STEAM Integrated Science Disciplines for Learning Planning for Primary School Students in Indonesia Towards the Era of Society 5.0 - Rafiuddin, Rafiuddin; Syarifuddin, Syarifuddin; Saparuddin, Saparuddin; Nurjihadin, Nurjihadin; Rahmat, Farah Alfian Ghofar (PT. Anagata Sembagi Education, 2024)
This research aims to find elements related to STEAM from 100 Google Scholar indexed articles resulting from scientific research. Elements related to STEAM can be implemented in elementary school students in facing the era of society 5.0. The method used in this research is the SLR (Literature Review System) PCR model (Planning, Conducting, Reporting) with the aim of systematically reviewing the literature to find elements related to STEAM based on research results from the last 7 years (2017-2024). The research results showed that other elements were compared with STEAM, such as language, social sciences, economics, religion, culture and literacy with the terms STREAM, SELAMeT, STREAME, STELAM and STEAMS and were even used as a basis for curriculum development such as in South Korea with the term WS-STEAM . Based on these findings, there are elements that can be used as a reference in developing learning plans in elementary schools towards the era of society 5.0 which are in accordance with the national basic education curriculum, especially in elementary schools in Indonesia, namely language, social (including culture and economics in social science learning ), religious, and literacy.